Clinical decision‐making for complex feeding decisions: A national survey of current approaches and perspectives. (31st July 2019) - Schwarz, Maria; Coccetti, Anne; Cardell, Elizabeth
Abstract: Objectives: Decision‐making around dysphagia management is becoming increasingly challenging due to the complexity of contexts associated with an ageing population. The current study explores current decision‐making practices used by speech language therapists (SLTs) surrounding contexts related to palliative care, dementia, neuro‐degenerative diseases, guardianship/family decisions, and other issues relevant to ongoing care of individuals with dysphagia. Methods: An exploratory prospective electronic survey of SLTs was conducted. A total of 202 respondents were eligible for inclusion. Results: Only 55% of respondents reported their workplace had a standard approach to documentation. Only 19% reported their service had a defined policy to support decision‐making, with only 28% reporting the existence of patient information brochures. Conclusion: Limited formal guidance or practice standards exist in the setting of complex dysphagia management, which limits the consistency of practice and clinical efficiency. This insight into current practices and perspectives supports the development of clinical guidelines.